RISK ANALYSIS LEVELS OF MUSCULOSKELETAL DISORDERS (MSDs) IN CONVECTION WORKERS BANGSRI VILLAGE, KARANGPANDAN - ipop Sjarifah; eka rosanti (Journal of Industrial Hygiene and Occupational Health, 2019)
Indonesia consists of formal (46,4%) and informal workers (53,6%). Informal sector industry has a role contributes to the national economy. Nowadays the informal sector industry does not get maximal attention in terms of occupational safety and health especially on musculoskeletal disorders by repetitive workers. The aim of this study is to analysis levels of musculoskeletal disorders in convection workers. This study used an observational analysis method with cross-sectional approach and the subject was the woman with 32 workers in Bangsri village, Karangpandan. The assessment of MSDs was used Nordic Body Map and Rapid Entire Body Assessment for work posture. The results showed that work period (0,034) and work posture (0,012) correlated significantly with Musculoskeletal disorders. Age, work period and work posture explains 47,1% of MSDs and the remaining 52,9% was explained by other variables that not included in this research. The conclusion of this research is 62,5% workers (20 people) experienced high levels of MSDs dan 37,5% workers (12 people) experienced moderate levels of MSDs. Exercise can reduce the risk of MSDs around the shoulder. Keywords: Musculoskeletal disorders, REBA, nordic body map, convection, risk factors